Comparison of five-year clinical outcomes of 524 cemented and cementless medial unicompartmental knee replacements - Martin, B; Rahman, A; Jenkins, C; Mohammad, H; Barker, K; Dodd, C; Jackson, W; Price, A; Mellon, S; Murray, D (Elsevier, 2021)
Aim To compare the outcomes of cemented and cementless Unicompartmental Knee Replacements (UKR) at 5 years after surgery.